Knowledge, Attitude and Practice regarding Tuberculosis among Diabetic Patients - Hossain, Md Delwar; Afroz, Farhana; Ahmed, Jamal Uddin; Amin, Md Kamrul; Quddus, Sharif Mohammad Ruhul; Islam, Shafiqul (BIRDEM Medical Journal, 2017)
Background: Tuberculosis (TB) is a major public health problem in Bangladesh. This study aimed to evaluate the current status of the knowledge, attitude, and health-seeking practice regarding TB amongst diabetic patients. Methods: This cross-sectional study was done in the Pulmonology OPD of Department of Internal Medicine, BIRDEM, 750 bedded Specialized Diabetic Tertiary Care hospital, Dhaka, Bangladesh from January to December 2015. Results: Out of 420 subjects (mean ±SD, age 51±12 years), 51% were male. Regarding educational status, 42% had primary and 34% had secondary education, while 12% graduated and 12% never attended school. More than half of the subjects belonged to the lower-middle income group. The proportion of poor, average and good score for knowledge were 19%, 66% and 15%, attitude 6%, 42% and 52% and for practice 11%, 82% and 7% respectively. Conclusion: Co-ordinated educational campaign with prioritized focus for poorer and less educated people needs to be considered for reducing tuberculosis transmission and better outcome with special attention to diabetic population. Birdem Med J 2017; 7(2): 127-131